Effects of global warming on wind energy availability - Ren, Diandong (American Institute of Physics, 2010)
The use of wind energy reduces our greenhouse gas emissions into the atmosphere. In this study, we proposed a generic power-law relationship between global warming and the usable wind energy (Betz’s law). The power law index (~4, region dependent) is then determined using simulated atmospheric parameters from eight global coupled ocean-atmosphere climate models (CGCMs). It is found that the power-law relationship holds across all eight climate models and also is time scale independent. Reduction of wind power scales with the degree of warming according to a generic power-law relationship. Thus, the earlier we switch to clean energy, and thereby decrease the global climate warming trend, the more cost-effective will be the harnessing of wind energy. This relationship is an area-averaged consequence of the reduced poleward temperature gradient as the climate warms during the 21st Century; it does not imply spatial uniformity over a region of interest.